A monolithic 180 nm CMOS dosimeter for wireless In Vivo Dosimetry. (January 2016) - Villani, E.G.; Crepaldi, M.; DeMarchi, D.; Gabrielli, A.; Khan, A.; Pikhay, E.; Roizin, Y.; Rosenfeld, A.; Zhang, Z.
Abstract: The design, fabrication and testing of a novel monolithic system-on-chip dosimeter fabricated in a standard 180 nm CMOS technology is described. The device, implementing a radiation sensor and an RF transmitter, is proposed to address the need for real-time In Vivo Dosimetry (IVD) of radiation during Linac radiotherapy sessions. Owing to its small size, of approximately 1 mm 3, such solution could be made in-body implantable and, as such, provide a much-enhanced high-resolution, real-time dose measurement to improve Quality Assurance (QA) in radiation therapy. The device transmits the related information on dose of radiation wirelessly to a remote receiver operating in the Medical Implant Communication Service (MICS) band. Comprehensive description of the various phases of this project, including the development of the radiation sensors and integrated RF transmitter to perform the readout, along with the final test results using a radiation beam, will be given. Highlights: A Monolithic Dosimeter for real time dosimetry during radiotherapy is proposed. The proposed device is 1 mm3 in size and could potentially be body implantable. The device includes a radiation sensor and RF readout, operating in the MICS band. Detailed tests have been performed under radiation beam in a clinical environment. Reported sensitivity is 1 cGy over 50 Gy, with an accuracy of better than 3%.